PENGEMBANGAN SISTEM PENDATAAN TAMU UNDANGAN BERBASIS ANDROID MENGGUNAKAN QR CODE PADA EVENT ORGANIZER - Suwandy Sumbogo; Syaiful Rahman; Izmy Alwiah Musdar (STMIK KHARISMA Makassar, 2019)
At a wedding there is a guest book to fill in so that the party organizers find out who the guests are. The length of filling in the guest book makes the queue quite long. The purpose of this study is to design and build an application system for android guest-based data collection using the QR Code that is used to replace the guest book filling. The research begins by designing ERD and Activity Diagrams. Then it is implemented into two programming languages namely PHP and Kotline and MYSQL database. Based on the results of the study, the author has succeeded in building an android-based guest guest data collection system application using the QR Code.